2003
DOI: 10.1038/sj.ejcn.1601821
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional risks in the Spanish population: results of the eVe study

Abstract: Objective: To determine the vitamin status of different groups within the Spanish population. Design: Pooled analysis of cross-sectional population nutritional regional studies and meta-analysis of smaller studies in population subgroups performed in Spain between 1990 and 1999. Subjects: In total, 10 208 participants in eight random population studies aged 25-60 y and participants in 76 studies included in the meta-analysis. Interventions: The data from different nutritional studies performed on sample popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Calcium status evaluation in Austria confirmed that the average intake was 834 + 422 mg/day [25]. Different international studies in Saudi Arabia, Finland, Turkey and Spain illustrated insufficient vitamin D in pregnant women's diets [14,[26][27][28]. Similarly, a study in Venezuela concluded that a high proportion of pregnant women do not take the recommended amounts of calcium [29].…”
Section: Discussionmentioning
confidence: 86%
“…Calcium status evaluation in Austria confirmed that the average intake was 834 + 422 mg/day [25]. Different international studies in Saudi Arabia, Finland, Turkey and Spain illustrated insufficient vitamin D in pregnant women's diets [14,[26][27][28]. Similarly, a study in Venezuela concluded that a high proportion of pregnant women do not take the recommended amounts of calcium [29].…”
Section: Discussionmentioning
confidence: 86%
“…Diversos estudios realizados con mayores en medio rural y urbano, han encontrado consumos alejados del patrón de dieta mediterránea en relación a la ingesta de carne, pescado, verduras, legumbres, grasas, vitaminas y minerales [22][23][24][25][26] . En el presente estudio, los porcentajes de usuarios que cumplen las recomendaciones son sólo aproximativas.…”
Section: Movilidadunclassified
“…The mapping of the prevalence of obesity in different population groups and analysis of trends over time is one of the valuable outcomes of such initiatives 11,12 . Autonomous regions such as the Basque Country, 13 Catalonia, 14 the Canary Islands, 15 Madrid, 16 Andalucia, 17 the Balearic Islands, 18 and Valencia 19 carried out nutrition surveys on random population samples using similar protocols, thus enabling the comparison or even pooling of data for analysis 20 . In some cases, more than one survey has been performed, allowing trend analysis to be conducted.…”
Section: Regional Experiences In Community Nutritionmentioning
confidence: 99%